Unveiling the Management of Community Health Centers and Its Impact on Service Quality and Patient Satisfaction in The Tabanan Regency of Bali - Suryawan, Made Agus; Maradona, Agus Fredy (Quantitative Economics and Management Studies, 2024)
This study seeks to examine the correlation between governance, service quality, and patient satisfaction at Tabanan III and Kerambitan II Community Health Centers (Puskesmas) in Tabanan Regency, Bali. Effective governance of Puskesmas, which includes planning, implementation, supervision, and evaluation, is pivotal in determining healthcare service quality. Service quality is assessed through dimensions such as timeliness, facility reliability, staff demeanor, and service accessibility, while patient satisfaction indicates the congruence between expectations and actual experiences with healthcare services. This research utilizes a quantitative methodology employing Partial Least Squares (PLS) and includes medical personnel and patients as participants. The results indicate that governance at Tabanan III and Kerambitan II Puskesmas positively affects both service quality and patient satisfaction. Additionally, healthcare service quality significantly influences. A significant discovery is that service quality mediates the relationship between governance and patient satisfaction, underscoring the critical role of good governance in improving overall healthcare service quality. This study underscores the necessity for enhanced focus on the execution of governance in accordance with Standard Operating Procedures (SOPs) and ongoing accreditation, as stipulated by Ministry of Health Regulation No. 34 of 2022. The results are anticipated to provide a basis for developing initiatives to strengthen governance and elevate service quality at Puskesmas, both in Tabanan Regency and in other locations with analogous issues. As a result, this study helps significantly to the creation of more effective primary healthcare services aimed at increasing community satisfaction.